The Role of Antiplatelet Therapy in Obese patients undergoing Percutaneous Coronary Intervention - Iftikhar Ahmad, Muhammad Saleem, Muhammad Khan Malik, Umair Abrar, Atif Ahmed Khan, Afzal Qasim, Nusrum Iqbal, Afsheen Siddiqi, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Obesity has become a major global health concern, with increasing prevalence worldwide, and is recognized as a significant risk factor for cardiovascular diseases. Objective: This study aims to evaluate the role of obesity in platelet reactivity, antiplatelet therapy efficacy, and major adverse cardiovascular events (MACE) in patients undergoing PCI. Methodology: This retrospective study was conducted at Timergara Teaching Hospital, Dir Lower during January 2022 to august 2022. A total of 235 patients were added in the study. Adult patients (aged 18–80 years) with a diagnosis of CAD who underwent PCI and were prescribed dual antiplatelet therapy (DAPT) post-procedure were included in the study. Patients with a history of contraindications to antiplatelet therapy, severe renal or hepatic dysfunction, and those who did not complete the follow-up period were excluded. Results: A total of 235 patients who underwent percutaneous coronary intervention (PCI) were added in the study. The obese group was older on average (62.3 ± 10.5 years vs. 59.4 ± 11.1 years, p = 0.045) and had a higher prevalence of hypertension (82% vs. 67%, p = 0.005), diabetes (56% vs. 40%, p = 0.018), and dyslipidemia (70% vs. 58%, p = 0.033). Additionally, the obese group had significantly higher levels of C-reactive protein (6.8 ± 3.2 mg/L vs. 4.2 ± 2.5 mg/L, p < 0.001) and insulin resistance (HOMA-IR 3.5 ± 1.2 vs. 2.1 ± 1.0, p = 0.002), indicating a more inflammatory and metabolically challenged state. The antiplatelet regimen between the obese and non-obese groups was largely similar, with both groups receiving 100% aspirin. There was no significant difference in the use of clopidogrel (70% in both groups), prasugrel (15% in obese vs. 14.8% in non-obese), or ticagrelor (15% in obese vs. 14.8% in non-obese), with all p-values above 0.9. Conclusion: It is concluded that obesity significantly increases the risk of major adverse cardiovascular events (MACE) in patients undergoing percutaneous coronary intervention (PCI). Our study demonstrates that obese patients exhibit higher platelet reactivity and a greater incidence of thrombotic events, despite receiving standard dual antiplatelet therapy. Keywords: Obesity, Antiplatelet Therapy, Adverse Cardiovascular Events, Percutaneous Coronary Intervention.